Apothecial Anatomy of some Parmelia Species of Namobudha, Kavrepalanchowk District, Central Nepal - Thapa, Khem B; Rajbhandary, Sangeeta (Journal of Natural History Museum, 2015)
The knowledge of lichen in Nepal was for the fi rst type introduced by Wallich’s collection done during 1820-21. The collection was mainly done from the eastern and central regions of the country. Lichens are found across all climatic regions of Nepal. They are characterized by the form in which they grow as they can grow on almost any substrate. They are usually identifi ed by its morphological characters, anatomy and colour test in order to separate genera as well as species. Now apothecial ontogeny and structural character is taken to recognise a family, genera and species. Altogether 31 species of different apothecial foliose and fruticose lichens were collected. Among them, 12 species of Parmelia were collected belonging to the family Parmeliaceace. This paper gives the difference of apothecial anatomy of fi ve species of the genus Parmelia collected from Namobudha, Kavrepalanchok district of central Nepal, which has helped in the identifi cation of the species. J. Nat. Hist. Mus. Vol. 26, 2012: 146-154